2016
DOI: 10.1161/circoutcomes.116.003122
|View full text |Cite
|
Sign up to set email alerts
|

Design, Challenges, and Implications of Quality Improvement Projects Using the Electronic Medical Record

Abstract: Postoperative atrial fibrillation (POAF) is a frequent complication of cardiac surgery, which results in increased morbidity, mortality, length of stay, and hospital costs. We developed and followed a process map to implement a protocol to decrease POAF: (1) identify stakeholders and form a working committee, (2) formal literature and guideline review, (3) retrospective analysis of current institutional data, (4) data modeling to determine expected effects of change, (4) protocol development and implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…While this current initiative focuses on post-PCI care for STEMI, numerous other risk calculators and models exist across the spectrum of cardiovascular disease. 1315 Within acute myocardial infarction, expansion of risk models to the triage of patients presenting with non-ST Elevation Myocardial Infarction and Unstable Angina for early discharge may be able to realize similar reductions in LOS and total costs, without compromising quality of care or patient outcomes. Similarly, as percutaneous approaches to structural and valvular heart disease increase, risk-based care delivery strategies may help to achieve higher value care.…”
Section: Discussionmentioning
confidence: 99%
“…While this current initiative focuses on post-PCI care for STEMI, numerous other risk calculators and models exist across the spectrum of cardiovascular disease. 1315 Within acute myocardial infarction, expansion of risk models to the triage of patients presenting with non-ST Elevation Myocardial Infarction and Unstable Angina for early discharge may be able to realize similar reductions in LOS and total costs, without compromising quality of care or patient outcomes. Similarly, as percutaneous approaches to structural and valvular heart disease increase, risk-based care delivery strategies may help to achieve higher value care.…”
Section: Discussionmentioning
confidence: 99%
“…In the current environment of quality improvement and focus on protocol driven care it is critical to evaluate these interventions using the value framework. (9) There are many pitfalls in designing and implementing and evaluating the success of quality improvement projects as described in a recent paper by Ebinger et al(26) However, these authors do not mention the significant investment of personnel hours to develop and successfully deploy a major service line wide initiative. While these estimates are difficult to identify and quantify, this prophylactic amiodarone protocol required over 100 hours of work from surgeons, nurses, and quality officers with an estimated cost of $3,530.…”
Section: Commentmentioning
confidence: 99%
“…Based on clinical trials and guidelines (17,18), we developed a decision support tool that prompts providers to prescribe prophylactic amiodarone to eligible patients prior to cardiac surgery. Although efficacy was previously shown in trials, this work demonstrated the effectiveness of this intervention, with a reduction in post-operative atrial fibrillation rates from 38% to 11% and an estimated cost savings of >$200,000 annually (19). …”
Section: Electronic Medical Recordmentioning
confidence: 73%